Analysis of Polysemy in Little Women (2019) Movie - Amoret, Zuvika; Wardoyo, Cipto (LPPM Universitas Dhyana Pura, 2025)
Polysemy is a linguistic term that describes when a word or phrase has multiple related meanings. Polysemy is part of the field of semantics, which studies the relationship between meanings in language. This research examined the presence of polysemy in the movie adaptation Little Women (2019) that directed by Greta Gerwig. The research method is descriptive qualitative, with analytical techniques applied to the source material, specifically the movie script. The theoretical framework for analyzing polysemy was based on Apresjan’s concept, which provides a comprehensive understanding of polysemy. The findings of this analysis include 12 data points, each consisting of two dialogues that present similar words but different meanings. The analysis concluded with the assertion that the Little Women (2019) movie exemplifies a multitude of polysemic uses related to semantics.